Engaging community voices to assess Kenya's strengths and limitations to support a child maltreatment prevention program. (January 2021) - Shanley, Jenelle R.; Armistead, Lisa P.; Musyimi, Christine; Nyamai, Darius; Ishiekwene, Martha; Mutiso, Victoria; Ndetei, David
Highlights: Mixed method study to assess Kenya's readiness to prevent child maltreatment. Kenya is 'moderately' ready to implement a child maltreatment prevention program. Kenya's strengths are existing child maltreatment knowledge and federal policies. Limitations include insufficient resources and lack of evidence-based programs. Results highlight important areas for program implementation planning. Abstract: Background: Preventing child maltreatment is a global mission of numerous international organizations, with parent support programs as the critical prevention strategy. In Kenya, 70 % of children are at risk of experiencing abuse and neglect, most often by their parents. Yet, there is a lack of evidence-based parent support programs, and a limited understanding of Kenya's capacity and infrastructures (e.g., policies, funding, service agencies) to support and sustain such programs. Objective: The purpose of this study was to assess systematically Kenya's strengths and limitations to implement a parent support program using a mixed-methods study design. Participants and Methods: Twenty-one community stakeholders from Kenya completed the World Health Organization's (WHO) Readiness Assessment for the Prevention of Child Maltreatment to understand Kenya's preparedness to undertake a prevention program. In addition, 91 participants (e.g., parents, community health workers, community leaders) took part in focus group discussions or individual interviews to understand existing support networks around parenting programs. Results: Kenya's overall 'readiness' score was comparable to the other countries that completed the WHO survey. The survey results revealed Kenya's strengths and limitations across the ten readiness dimensions. Several themes emerged from the focus groups and interviews, including the diverse sources of support for parents, specific programs available for parents, and gaps in services offered. Conclusions: The results document ways to build upon Kenyan's existing strengths to facilitate implementation of an evidence-based prevention program. These results also highlight the significant need to understand local context when adapting parenting programs for low/middle income countries (LMICs).